Розвиток комунікативної компетентності студентів спеціальності 014 «Середня освіта» під час вивчення дисципліни «Партнерство і професійна комунікація вчителя» - Равлюк, Тетяна (My University, 2024)
Nurturing effective communication skills among future educators is crucial for fostering successful socialization and conflict resolution abilities in their students. This article explores the development of communication competence in students specializing in secondary education through the course «Partnership and Professional Communication of a Teacher». The article delves into the connection between «communication» and «communication competence», highlighting the significance of «communication abilities» and «communication qualities» for active participation in society. It outlines the three core components of communication competence: cognitive, emotional, and behavioral. To assess the level of communication skills development, a survey was conducted among students pursuing a master's degree in secondary education. The results revealed that 65% (28 students) demonstrated a high level of communication skills, while 35% (15 respondents) exhibited a lower level. Aiming to enhance their own speech and promote effective communication, students were tasked with a project: Identify a communicative feature of speech culture (quality, characteristic, ability, or habit related to communication) that requires improvement (development or overcoming). Determine methods and approaches for improvement. Design and implement an action plan. Analyze the outcomes. The majority of students focused on: enhancing speech expressiveness, overcoming public speaking fear and communication barriers, improving speech clarity, content, accuracy, logical sequence, and richness, developing effective listening skills, mastering emotional control in communication. Student quotes reflecting on the project highlight their commitment to continuous improvement in communication skills.
Keywords: communication, communication skills, communication qualities, communication competence of personality